108k views
2 votes
To make q subject of the formula
a(q-c)=d

User Indy
by
5.4k points

1 Answer

4 votes
a(q-c)=d
a(q-c)/a=d
(q-c)=d/a
(q-c+c)=d/a+c
q=d/a+c

Explanation
a is multiplying everything in the bracket, so to get it on the other side of the equation, you multiply, the ‘a’ is dividing the ‘d’ because anything that is done on one side should be done on the other
‘c’ is being subtracted from ‘q’ so we do the opposite which is addition in order to cancel them out and get the ‘q’ by itself
User Timdisney
by
5.9k points